3D FEM simulation of SAW resonators using hierarchical cascading technique and general purpose graphic processing unit. (13th June 2019) - Li, Xinyi; Bao, Jingfu; Qiu, Luyan; Matsuoka, Naoto; Omori, Tatsuya; Hashimoto, Ken-Ya
Abstract: This paper proposes an application of a general purpose graphic processing unit (GPGPU) to the finite element method analysis based on the hierarchical cascading technique (HCT). It is proved that GPGPU can accelerate the HCT significantly, especially for large scale problems. Thanks to significant acceleration, full three-dimensional simulation is possible for practical surface acoustic wave (SAW) device structures. Besides admittance curve, the displacement field is calculated. It is shown that SAW scattering occurs at the boundary at busbar spaces between the interdigital transducer (IDT) and reflector regions.